IMPLEMENTASI BERMAIN PERAN DALAM UPAYA MENGEMBANGKAN FOKUS BELAJAR PADA ANAK USIA 4-5 TAHUN DI KB MUHAMMAD SHODIQ - Firdaus, Jannatul; ainol; Hafidlatil Kiromi, Ivonne (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to describe the implementation of role-playing activities in developing the learning focus of 4–5-year-old children at the Muhammad Shodiq Kindergarten. This study used a qualitative approach with a descriptive research type. The research subjects consisted of teachers and 4–5-year-old children at the Muhammad Shodiq Kindergarten. Data collection techniques used in this study included observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman data analysis model, which includes data reduction, data presentation, and conclusion drawing. The results show that the implementation of role-playing activities was carried out through three main stages: planning, implementation, and evaluation. In the planning stage, the teacher determined the game theme that aligns with the learning theme and prepared media and props to support the role-playing activities. In the implementation stage, the teacher explained the game flow and assigned roles to the children according to the predetermined theme. During the activity, the children appeared more active, enthusiastic, and directly involved in the learning process. Role-playing activities also helped children improve their ability to focus on learning, such as paying attention, following teacher instructions, and completing the activity to completion. Based on the research findings, it can be concluded that role-playing activities can be an effective learning strategy for developing early childhood learning focus and creating a more engaging and enjoyable learning process. Keywords: role-playing, learning focus, early childhood.